Unlocking innovation: Assessing the role of Agricultural R&D in Latin America and the Caribbean - Nin-Pratt, Alejandro; Stads, Gert-Jan; de los Santos, Luis; Muñoz, Gonzalo (Inter-American Development Bank, 2023)
This report presents a comprehensive analysis of public agricultural research and development (R&D) in Latin America and the Caribbean (LAC), focusing on the contextual factors influencing agricultural R&D investment and their implications for agricultural productivity growth. The analysis combines new data for ten LAC countries collected by the International Food Policy Research Institute's (IFPRI's) Agricultural Science and Technology Indicators (ASTI) program with support from the Inter-American Development Bank (IDB), with existing ASTI and other datasets. By integrating these various datasets, the report provides an in-depth examination of recent trends in public agricultural research spending, capacity, and outputs across the LAC region. Despite the demonstrated high returns on agricultural R&D investments, LAC countries continue to lag in allocating sufficient resources to this critical area. The traditional agricultural research model faces major challenges in keeping pace with the evolving agricultural landscape and food system more broadly.